On the gold-Catalyzed generation of vinyl cations from 1,5-diynes - Wurm, Thomas; Bucher, Janina; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K. (Angewandte Chemie. International edition, 2017)
Conjugated 1,5-diynes bearing two aromatic units at the alkyne termini were converted in the presence of a gold catalyst. Under mild conditions, aryl-substituted dibenzopentalenes were generated. Calculations predict that aurated vinyl cations are key intermediates of the reaction. A bidirectional approach provided selective access to the angular annulated product in high yield, which was explained by calculations.